Platform Therapy Compared with Natalizumab for Multiple Sclerosis: Relapse Rates and Time to Relapse Among Propensity Score-Matched US Patients - Johnson, Barbara H. (CNS Drugs, 2015)
BACKGROUND: Multiple sclerosis (MS) registry data, primarily from Europe, suggest that treatment with natalizumab delays time to relapse compared with platform therapy (interferon beta/glatiramer acetate). OBJECTIVE: This study uses US administrative claims data and propensity score matching (PSM) to compare relapse rates and time to relapse among patients with MS using either platform therapy or natalizumab. METHODS: Adults with MS receiving either platform therapy or natalizumab between January 1, 2009 and April 1, 2012 were identified in the Truven Health MarketScan(®) Research Databases. Patients were included if they had 12 months of continuous enrollment both before and after the index date (the first claim for either drug cohort) and had 12 months of claims data suggesting consistent treatment adherence during the follow-up period. Characteristics used in PSM included demographics, selected comorbidities and concomitant medications, MS severity, baseline relapse rates, and expenditures. A relapse was defined as an MS-related hospitalization or corticosteroid use. RESULTS: A total of 882 patients were matched. Relapse occurred among significantly fewer patients in the natalizumab group (26.5 %) than platform therapy (35.5 %, p < 0.001) (hazard ratio 0.69; 95 % CI 0.59–0.82). Relapses were also significantly later for those on natalizumab (308 vs 283 days without relapse, p < 0.001). CONCLUSION: Treatment with natalizumab was associated with a significantly lower risk and rate of MS relapse and longer MS relapse-free time compared with platform therapies.